2011
DOI: 10.3109/14767058.2011.598588
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, treatments, and outcomes associated with prolonged hyperemesis gravidarum

Abstract: Objective To identify factors associated with prolonged Hyperemesis Gravidarum (HG). Study Design About 395 women completed a survey regarding pre-existing conditions, treatments and outcomes. Responses were compared using two-sided t-test or the F-test. Results Participants with prolongs HG are slightly younger and weight more. Pre-existing factors associated with prolonged HG include allergies and a restrictive diet. Prolonged HG is associated with hematemesis, dizziness, fainting and antiemetic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 31 publications
1
68
1
1
Order By: Relevance
“…It still remains elusive whether such diff erences can be attributed to genetic factors related to ethnicity aff ecting outcomes in women with HG, or whether they could be a result of cultural diff erences aff ecting reporting of symptomology. HG is associated with elevated levels of PAPP-A and free β -hCG, as reported by a recent study in the Turkish population (Derbent et al 2011) and numerous other parameters have been analysed in the literature; among those are allergies suggesting a possible autoimmune component and a restrictive diet (Mullin et al 2012). Helicobacter pylori have also been proposed as a possible aetiological factor for HG but this remains controversial (Karadeniz et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…It still remains elusive whether such diff erences can be attributed to genetic factors related to ethnicity aff ecting outcomes in women with HG, or whether they could be a result of cultural diff erences aff ecting reporting of symptomology. HG is associated with elevated levels of PAPP-A and free β -hCG, as reported by a recent study in the Turkish population (Derbent et al 2011) and numerous other parameters have been analysed in the literature; among those are allergies suggesting a possible autoimmune component and a restrictive diet (Mullin et al 2012). Helicobacter pylori have also been proposed as a possible aetiological factor for HG but this remains controversial (Karadeniz et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Mullin et al (24) concluded that no significant differences were observed between the control group and the HG short-duration group (HG symptoms that resolved before 27 gestational weeks). However, members of the HG long-duration group (symptoms lasting until birth) were significantly more likely to be younger and weigh more than members of the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the aetiology of HG was poorly understood and it was thought to be caused by endocrine, infectious, psychosocial, and hereditary factors 4. However, recent studies in twins showed that severity and duration of NVP are highly genetic 8.…”
Section: What Causes It?mentioning
confidence: 99%
“…A meta-analysis of observational studies showed other risks during pregnancy include low birth weight (<2500 kg; odds ratio 1.42; 95% confidence interval 1.27 to 1.58), preterm labour (odds ratio 1.32; 95% confidence interval 1.04 to 1.68), small for gestational weight babies (odds ratio 1.28; 95% confidence interval 1.02-1.60) 42938. Case reports have identified vitamin deficiencies 39.…”
Section: What Are the Risks?mentioning
confidence: 99%
See 1 more Smart Citation